The Ability of The Seventh Grade Students of SMP Budi Murni 2 on Using Present and Past Tenses - Dabukke, Yesmaria Kembar; Lumban Raja, Viator; Pangaribuan, Jontra Jusat (Journal of Applied Linguistics, 2025)
Tense is a verb form to show an action within a certain time. Grammar is the rules in a language for changing the form of words and joining them into sentences to create meaning. To make a good composition, the students must be able to master and apply the grammar correctly, especially aboit tenses used. This research is focused on the ability students on the using simple present and simple past tenses. The purpose of this study is to find out and to know the ability the students. In this study, the writer took the seventh grade students of SMP Budi Murni 2, consisting 60 students as the sample. The data were analyzed with quantitative method. The result of the data shown that the seventh grade students are not yet able to use simple present and simple past because their average score is only 56.08 whereas the minimum requirement completion is 75. In other words, they are still far from the target score. Based on the result of the research is suggested that the student must study hard. And the teacher should give home assignment for the students.